PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN SARANA PRASARANA TERHADAP MUTU PENDIDIKAN DI SMPN 1 OMBEN KABUPATEN SAMPANG - Risnanto Saputro; Fatimah Riswati; Chamariyah (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
The purpose of study are: 1) Describe the leadership style, organizational culture, infrastructure and quality of education at SMPN 1 Omben, Sampang Regency; 2) Test and analyze the partial influence of the leadership style, organizational culture and infrastructure on the quality of education at SMPN 1 Omben, Sampang Regency; 3) Test and analyze the simultaneous influence of the leadership style, organizational culture and infrastructure on the quality of education at SMPN 1 Omben, Sampang Regency. The number of research samples as many as 34 people, the sampling methods using the census sampling method. Analysis tools Using SPSS. The results showed that: 1) Partially, leadership style, organizational culture, and infrastructure have a significant influence on the quality of education at SMPN 1 Omben, Sampang Regency. So that in this case the first hypothesis is accepted and its validity is proven; 2) Simultaneously, leadership style, organizational culture, and infrastructure have a significant influence on the quality of education at SMPN 1 Omben, Sampang Regency. So that in this case the second hypothesis is accepted and its validity is proven